Growth and morphological responses of Halophila beccarii to low salinity - Dang Thi Le Xuan, Xuan; Phan , Thi Thuy Hang; Hoang , Cong Tin; Ton, That Phap; Luong , Quang Doc (Hue University Journal of Science: Natural Science, 2022)
Halophila beccarii Ascherson is classified as a threatened seagrass species by IUCN because of the reductive tendency of ​​its distribution area. This seagrass is considered a euryhaline species adapted to a wide range of salinities from freshwater and brackish water to marine water. Previous studies showed that the species tends to grow better under low salinity; however, its optimum salinity has not been determined. In Vietnam, H. beccarii grows in habitats with low salinity (0–20 ppt). The results show that salinity affects the growth, survival rate, shoot density, biomass, and morphological characteristics of the grass. The leaf dimension is more prolonged and broader; the petiole and shoot length are longer at 10 ppt salinity. In contrast, both the number of shoots and biomass peak at 5 ppt and decrease at lower and higher salinities. The study reveals that H. beccarii can grow better under mesohaline conditions than freshwater and hypersaline conditions with an optimum salinity at 5–10 ppt. These findings would explain the species’ distribution dynamics in coastal environments and be helpful information for conserving the seagrass populations in habitats with fluctuating salinity as coastal lagoons in Central Vietnam.